9x+6-3x-1=-103

Simple and best practice solution for 9x+6-3x-1=-103 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+6-3x-1=-103 equation:



9x+6-3x-1=-103
We move all terms to the left:
9x+6-3x-1-(-103)=0
We add all the numbers together, and all the variables
6x+108=0
We move all terms containing x to the left, all other terms to the right
6x=-108
x=-108/6
x=-18

See similar equations:

| (2x+9)+5x=180 | | 60x-50+30x-250=-8x-20+25x | | -w/5-2=8 | | (-3x+80)+23=5x-7 | | 2x-10-3x-4=-22 | | 0.75n-18=0.25(n-16) | | (9/4)(w-(1/9))=7/2 | | -5/v-5=-8 | | 20x-3=40x+9 | | 129-x=250 | | 19f+23-7f=187+-39 | | -2x-10-3x-4=-22 | | 24=w+2w | | -x/7=-54 | | 1.2=-32b | | -4+2/5x=18 | | 9f+3=22 | | 26=90n | | 2(3-2x)=4 | | -3x-12+x+1=-23 | | 3/12d=22/12 | | -10n+3(8+8n)=6(n-4 | | 3/12d=211/12 | | -1/2x+6=13 | | (-4+h)=3h | | 3x+5-8=-18 | | T=4/5n-72 | | 4-(x-2)+3(2x-5)=11 | | 2(1+2m)=1/2(8+20m) | | -4m-10=6 | | z/17-1=-8 | | 7,134+d=18,010 |

Equations solver categories